Prevalence of hepatitis C virus in adult population in the Czech Republic - time for birth cohort screening - Chlibek, Roman; Smetana, Jan; Sosovickova, Renata; Gal, Peter; Dite, Petr; Stepanova, Vlasta; Pliskova, Lenka; Plisek, Stanislav (PloS one, 2017)
Chronic hepatitis C is curable disease. Low detection rate could be one of the reasons of poor treatment uptake. It is important to identify HCV prevalence and anti-hepatitis C virus (HCV) positive patients in population by effective screening strategy such as risk-based or birth cohort screening programs. There are no national population-based estimates of the HCV prevalence in the Czech Republic (CZ). The most recent seroprevalence survey determined a prevalence of positive anti-HCV antibodies of 0.2% (in 2001). The aim of the study was to determine the seroprevalence of HCV, HCV viraemia and HCV genotype in the CZ adult population. We also estimated the number of persons living with chronic hepatitis C in CZ. The examined group included 3000 adults, 18-90 years of age enrolled in 2015. All serum samples were examined to determined anti-HCV antibodies positivity, HCV-RNA positivity and genotypes. Of the 3000 samples, 50 were found to be anti-HCV-positive, for a seroprevalence of 1.67% (2.39% in males, 0.98% in females). The overall prevalence of positive HCV RNA was 0.93%: 1.5% in males, 0.39% in females. HCV genotype (GT) 1a was determined in 25%, GT 1b in 25% and GT 3a in 46%. Since 2001, the HCV seroprevalence has increased 8-fold. The highest HCV seroprevalence occurred in males aged 30-44 years. We can estimate that there are more than 140,000 people with HCV antibodies and more than 80,000 people with chronic hepatitis C living in the CZ. The introduction of birth cohort HCV screening could be beneficial for the country.
Keywords: Male; plošný screening; RNA virová; lidé středního věku; Prevalence; senioři nad 80 let; genotyp; Aged, 80 and over; chronická hepatitida C; Hepatitis C Antibodies; Humans; Middle Aged; senioři; Hepacivirus; Česká republika; mužské pohlaví; prevalence; Czech Republic; Female; Seroepidemiologic Studies; RNA, Viral; mladiství; Aged; Age Distribution; séroepidemiologické studie; Hepatitis C, Chronic; ženské pohlaví; mladý dospělý; Adult; Young Adult; Mass Screening; Viremia; viremie; věkové rozložení; Adolescent; dospělí; lidé; Genotype; hepatitida C - protilátky